Arthroscopic findings in the painful tennis wrist - Schabus, R. (2000)
Some of the most serious problems that affect tennis players are micro-injuries/overuse-syndromes of the wrist. Painful limitation of dorsal extension and often, inability to use the racket forcefully, lead to multiple treatment attempts, ranging from intra-articular injections to operative treatment. This situation is often combined with increased laxity of the wrist. Inability to extend the wrist and use it in forceful motion disables many tennis players to the extent that they can no longer play. The wrist problems involve impingement of hypertrophied synovia between capsular ligaments and bone. The reactive synovitis increases with cartilage damage, loose bodies and triangular disc problems. Arthroscopic treatment would therefore appear to be the most useful treatment for the painful wrist. This study involved 12 patients with a two to three-year history of wrist problems. Patients with injured triangular disc syndromes and carpal instabilities were excluded. All patients had previously received conservative treatment, with rest, bracing, anti-inflammatories, intra-articular injections and physiotherapy, without relief of the wrist problems. Prior to surgical intervention, all wrists were examined with MRI and X-ray, and carpal function tests were performed. All patients underwent arthroscopic surgery with arthroscopic resection of the dorsal synovia, resection of intra-articular fragments and smoothening of cartilage defects. After arthroscopic surgery, the wrist was immobilized for two weeks. This was followed by intensive muscle strengthening physiotherapy and bracing when patients started practicing tennis again. The arthroscopic findings showed 9 cartilage lesions, 2 loose bodies and in all cases, hypertrophied synovial membrane of the dorsal wrist capsule. All patients returned to playing tennis. The level of performance returned to that prior to the onset of wrist pains in all but two patients. Three of the patients still have some pain when playing tennis. The conclusion is that dorsal arthroscopic synovectomy and resection of loose cartilage fragments of the wrist is an effective treatment of over-use syndromes of the wrist in tennis players. The clinical results are better when the diagnosis indicates arthroscopy and when surgery is performed at an early stage.